2020
DOI: 10.1007/s10661-020-8153-1
|View full text |Cite
|
Sign up to set email alerts
|

Can portable air quality monitors protect children from air pollution on the school run? An exploratory study

Abstract: With air quality issues in urban areas garnering increasing media attention, concerned citizens are beginning to engage with air monitoring technology as a means of identifying and responding to the environmental risks posed. However, while much has been written about the accuracy of this sensing equipment, little research has been conducted into the effect it has on users. As such, this research deploys coping theory to explore the specific ways in which portable air quality sensors influence user behaviour. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Although some studies relied solely on sensor measurements [42, 43, 45, 46 and 89] more studies combined sensor measurements with interviews [61,62] or questionnaires [44, 48, 63 and 64]. Eight studies applied only qualitative methods (e.g., interviews, focus groups or analyses of journal entries [39,55,[65][66][67]). Nine studies combined qualitative and quantitative methods to assess the outcome/s of exposure feedback (i.e., mixed methods approach) [62,[68][69][70].…”
Section: Methods Of Outcome Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies relied solely on sensor measurements [42, 43, 45, 46 and 89] more studies combined sensor measurements with interviews [61,62] or questionnaires [44, 48, 63 and 64]. Eight studies applied only qualitative methods (e.g., interviews, focus groups or analyses of journal entries [39,55,[65][66][67]). Nine studies combined qualitative and quantitative methods to assess the outcome/s of exposure feedback (i.e., mixed methods approach) [62,[68][69][70].…”
Section: Methods Of Outcome Measurementmentioning
confidence: 99%
“…For some participants, the feedback increased their confidence, e.g., to talk to others about the topic or to reduce their exposure [39, 49, 73 and 74]. In other cases, however, participants reported that their increased awareness was uncomfortable due to feelings of powerlessness and low selfefficacy to control their exposure [65]. Apart from knowledge gains, receiving feedback about smoking at home and its health impacts also led to a significant increase in risk perception and concern regarding health impacts [55, 62, 74 and 76].…”
Section: Knowledge Awareness and Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, communicating personal vulnerability via personalised air quality data has been found to help individuals revisit their prior perceptions about air pollution and demonstrate the impact individual actions have on personal exposures [50]. In another study, providing participants with personal sensors on the commute to school resulted in the majority identifying air pollution as a 'threat', caused many to perceive air pollution as a greater 'problem' on the school commute than previously thought and resulted in the majority of participants taking protective action in response to the monitoring data [51].…”
Section: Traditional Mechanisms To Promote Individual Exposure Minimi...mentioning
confidence: 99%
“…Some studies suggest that micro-monitors detecting ambient PM2.5 may help change behaviour but these studies do not use rigorous experimental methods (N Klepeis, S. Hughes, et al 2013;Wong-Parodi et al 2018;Heydon et al 2020;Iribagiza et al 2020). …”
mentioning
confidence: 99%